Analisis Pengaruh Program Flash Sale dan Discount Terhadap Impulsive Buying pada Generasi Milenial Pengguna Shopee - Novianda Adisti; Puji Isyanto; Neni Sumarni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The ease with which people can access the internet and the increasing affordability of smartphones to the lower and middle classes have enabled digital technology to capture a large market share. This is demonstrated by the increasing number of unicorn startups in Indonesia, such as Shopee. Shopee is very active in utilizing online marketing strategies, especially in carrying out promotions in the form of flash sales and discounts to attract the attention of Shopee users. This research aims to evaluate the effect of flash and discount programs on impulsive buying among the millennial generation of Shopee users. The research method uses SPSS 23 analysis with a population of residents in Bumi Mutiara Indah. A sample of 86 respondents was taken using the Slovin formula (10% error rate). The research results show that flash sale and discount programs significantly influence impulse purchases.